PENGARUH KEDISIPLINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. PDAM SEMARANG (Students' Journal of Economic and Management, 2013)
This study aims to examine and analyze the effect of labor discipline and motivation on employee performance PT. PDAM Semarang Data collection is done through questionnaires and performed on 100 employees PT. PDAM Semarang. Inside,it is the researchers did not use samplinghe tecniquesthe method is a method of census data and testing tecniques used in this study include the validity of the test by using a person correlation result showed that the calculated value of r > r table,then the person is declared validcorrelation. Futher using multiple regression between thesee variables. The result is a hypothetical outcome that shows discipline and a significant positive effect on employee performance, while positive and significant effect of motivation on employee performance.